2014
DOI: 10.18632/oncotarget.2262
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 dependent H3K27me3 is involved in epigenetic silencing of ID4 in prostate cancer

Abstract: Inhibitor of DNA binding/differentiation protein 4 (ID4) is dominant negative helix loop helix transcriptional regulator is epigenetically silenced due to promoter hyper-methylation in many cancers including prostate. However, the underlying mechanism involved in epigenetic silencing of ID4 is not known. Here, we demonstrate that ID4 promoter methylation is initiated by EZH2 dependent tri-methylation of histone 3 at lysine 27 (H3K27me3). ID4 expressing (LNCaP) and non-expressing (DU145 and C81) prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 55 publications
(73 reference statements)
2
44
0
Order By: Relevance
“…These findings were in accordance with previous studies that showed an increase in the enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2)-mediated histone methyl transferase activity in PCa [68][69][70][71][72]. Among the perturbed metabolites, sarcosine was significantly increased during disease progression from normal through localized to metastatic PCa, and was detectable in urine.…”
supporting
confidence: 92%
“…These findings were in accordance with previous studies that showed an increase in the enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2)-mediated histone methyl transferase activity in PCa [68][69][70][71][72]. Among the perturbed metabolites, sarcosine was significantly increased during disease progression from normal through localized to metastatic PCa, and was detectable in urine.…”
supporting
confidence: 92%
“…The evidence for regulation of DNMT1 by miR-342 is further supported by studies on prostate cells, where both ID4 and DNMT1 show interactions in both cell lines and prostate cancer tissue (47) where up-or down-regulation of CEACAM1 is also observed (51). Taken together, the fine-tuning of the lumen formation program involves two negative acting signals.…”
Section: Discussionmentioning
confidence: 74%
“…Cells-The ID4 promoter has been shown to be hypermethylated in prostate cancer via recruitment of EZH2 and DNMT1 that methylate histone 3 at lysine 27, and a CpG island in the ID4 promoter, respectively (47). Although the EVL promoter is hypermethylated in many cancers, leading to the coordinated suppression of both EVL and miR-342 (27), we must conclude that the opposite situation exists in MCF7 cells because both EVL and miR-342 expression are high (Fig.…”
Section: Dnmt1 Is a Target Of Mir-342 In Mcf7mentioning
confidence: 99%
“…In addition, this knowledge may shed light on understanding how ID4 is down-regulated during tumorigenesis. Because ID4 gene silencing by hyper-methylation has been widely reported (13), it was likely that the same situation exists in MCF7 cells. To test this idea, parental MCF7 cells were treated with a combination of 5-aza-2Ј-deoxycytidine (DAC), a DNMT inhibitor, and trichostatin A (TSA), a histone deacetylase inhibitor to effect global chromatin re-modeling and demethylation.…”
Section: Id4 Gene Hyper-methylation and Silencing Can Be Reversed By mentioning
confidence: 97%
“…The ID4 gene that is frequently silenced by hypermethylation (13,14) is indeed hypermethylated in parental MCF7 cells, suggesting that this silencing affects lumen formation, a critical pathway in maintaining the normal differentiated state of mammary epithelial cells. The fact that introduction of CEACAM1 into MCF7 cells that have lost the ability to express CEACAM1, restores ID4 expression suggests a direct link between CEACAM1 expression and relief of the gene silencing of ID4.…”
mentioning
confidence: 99%